PEMBERDAYAAN PETANI DENGAN PUPUK ORGANIK UNTUK MENINGKATKAN HASIL PERTANIAN DI KABUPATEN SORONG - Ajang Maruapey; Mira Herawati Soekamto; Ferdinan Nuru; Nurlela Nurlela (Jurnal Pengabdian Mitra Masyarakat, 2023)
As an effort to educate the lives of people in rural areas, the government and higher education institutions (PT) always collaborate and synergize to provide assistance and counseling to the community, especially farmers so that farmers' skills and knowledge of innovation and new technology can be increased to increase production yields and family economic income. . Community service activities (PkM) will be held on December 26, 2022. The aim of PkM is to transfer fertilization science and technology that is environmentally friendly, while at the same time utilizing it for the sustainability of farming land. The method used in PkM activities is in the form of counseling in the form of lectures and cultivation assistance. The results achieved from the PkM activities are the creation of better farming conditions compared to the previous conditions, where in an organic crop cultivation system it is known that the land is gradually being improved. Even so, massive assistance is needed to develop farmer awareness and enthusiasm to more intensively implement organic-based farming systems in a sustainable manner.